2015
DOI: 10.15412/j.ptj.07050308
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Quadriceps and Hamstring Co-Contraction Following Landing in Microgravity Condition: Comparing Females with Different Activity Levels

Abstract: Purpose: This study aimed to examine the differences in the co-activation of the rectus femoris (RF) and biceps femoris (BF) using the co-contraction index (CI) in aquatic and land environments during a drop-landing task in active and non-active females. Methods:In this casual-comparison study, 10 active and 10 non-active females volunteered to participate. The CI was calculated from recorded surface electromyographic (SEMG) activity of the RF and BF. To calculate CI, the amount of overlap between the linear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Microgravity studies using electromyography (EMG) of the lower limb have demonstrated that during eccentric muscle contraction, the tibialis anterior is highly activated (Kenyon and Young, 1986). Other research has shown poor co-contraction of antagonistic paired muscles, as well as excessive activity of superficial lumbosacral muscles during simulated microgravity experiments (Belavý et al, 2007;Sadeghi et al, 2016). Therefore, analyzing other aspects of the sensorimotor system in conjunction with proprioception has the potential to provide further insight to physiological changes in novel gravitational environments.…”
Section: Introductionmentioning
confidence: 99%
“…Microgravity studies using electromyography (EMG) of the lower limb have demonstrated that during eccentric muscle contraction, the tibialis anterior is highly activated (Kenyon and Young, 1986). Other research has shown poor co-contraction of antagonistic paired muscles, as well as excessive activity of superficial lumbosacral muscles during simulated microgravity experiments (Belavý et al, 2007;Sadeghi et al, 2016). Therefore, analyzing other aspects of the sensorimotor system in conjunction with proprioception has the potential to provide further insight to physiological changes in novel gravitational environments.…”
Section: Introductionmentioning
confidence: 99%